Solve the following linear equation:
∴                                Â
Check:Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â LHS =
                                              Â
                          =
                                                 Â
                                                  =
                           Â
                           RHS =
                              Â
                  =
                                  =
                           Â
 ∴             LHS = RHS
Simplify and solve the following linear equation:
3(5z - 7) - 2(9z - 11) = 4(8z - 13) - 17